2016
DOI: 10.1097/md.0000000000005388
|View full text |Cite
|
Sign up to set email alerts
|

Physician perspectives on de-intensifying diabetes medications

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 32 publications
0
24
1
Order By: Relevance
“…Physicians' agreement with the concept of individualising HbA1c goals did not significantly differ between physicians from different demographics. Unlike a previous study, which showed that female physicians had a higher possibility of initiating such conversations with their patients, 23 we found that male physicians showed a higher possibility of initiating conversations about antidiabetic therapy de‐intensification compared with females. Previous studies showed that male physicians usually have shorter durations of consultations with their patients than female physicians, ask them less questions, and do not discuss physical activities and lifestyle with them 36‐40 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Physicians' agreement with the concept of individualising HbA1c goals did not significantly differ between physicians from different demographics. Unlike a previous study, which showed that female physicians had a higher possibility of initiating such conversations with their patients, 23 we found that male physicians showed a higher possibility of initiating conversations about antidiabetic therapy de‐intensification compared with females. Previous studies showed that male physicians usually have shorter durations of consultations with their patients than female physicians, ask them less questions, and do not discuss physical activities and lifestyle with them 36‐40 .…”
Section: Discussioncontrasting
confidence: 99%
“…Genere and colleagues' questionnaire, which was developed to understand physicians' awareness of, agreement with and their practices of individualising HbA1c goals and antidiabetic treatment de‐intensification. In addition, it has been used to identify HbA1c level at which physicians start treatment de‐intensification and what important patient factors that motivate them to consider such practice 23 . In addition, Grant and colleagues' questionnaire, which was used to assess factors affecting physicians' treatment choice when prescribing antidiabetic treatment for patients with type 2 DM has been used 24…”
Section: Methodsmentioning
confidence: 99%
“…A physician survey by Genere et al. found that targeting adherence is both impactful for treatment success and difficult to implement [ 28 ]. 2 European studies observed higher adherence rates for monitoring adherence than for screening adherence parameters [ 9 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason could be the familiarity and awareness about the individualized HbA1C goals in patients with T2D among older physicians. In a recent study, physicians widely used the concept of individualizing glycemic goals 24 .…”
Section: Discussionmentioning
confidence: 99%